Age-dependent transcriptional and epigenetic alterations in mouse hepatocytes - Sharma, Ankur (Nanyang Technological University, 2022)
Aging is associated with declining body function and heightened risks of various diseases. The liver is the largest solid internal organ responsible for functions ranging from metabolism to detoxification. Hepatocytes perform most liver functions and hepatocyte polyploidization is a characteristic feature of adult liver. This thesis presents the first integrative study of age-dependent transcriptomic changes in mouse hepatocytes and their epigenetic regulation. Using purified mouse hepatocytes of different ploidy, we first established differences in their gene expression patterns by RNA sequencing. Similarly, we identified age-associated molecular signatures in hepatocytes of different age groups. ChIP-sequencing of multiple histone post-translational modifications revealed a differential signal pattern of H3K27me3 at genic and non-genic regions in 8-week and 32-week hepatocytes which may be key in age-associated gene regulation. Moreover, we observed that A/B chromatin compartment is largely invariant suggesting the robustness of spatial genome organisation at Mb-scale in these age groups.